Effect of ultrasound on the functional properties and structural changes of chicken liver insoluble proteins isolated by isoelectric solubilization/precipitation - Rongrong Mao; Guoyuan Xiong; Haibo Zheng; Jun Qi; Chunhui Zhang (Ultrasonics Sonochemistry)
The studies investigated the effects of different ultrasonic powers (180, 360 and 540 W) on the functional properties and structural changes of chicken liver insoluble proteins (CLIPs) isolated by isoelectric solubilization/precipitation (ISP) (with alkaline solubilization at pH 11.0 and pH 12.0 respectively, and acid precipitation at pH 5.5). Results indicated that ultrasonic significantly increased the solubility of ISP-isolated CLIPs, and narrowed the particle size distribution of D3,2 and D4,3 (P < 0.05). The highest solubility was observed at pH 11.0 and 360 W ultrasound treatment, reaching 77.26 %. The ultrasonic with 360 W exhibited higher shear stress and apparent viscosity. Spectroscopy revealed that compared to without ultrasonic treatment, there was an increase in β-sheet and random curling content accompanied by a decrease in β-turn and α-helix structure when ultrasonication. Ultrasound altered the tyrosine hydrophobic residues to be exposed to the surface of the ISP-isolated CLIPs, thus improving the hydrophilicity. Overall, ultrasound combined with ISP treatment effectively improved the functional properties of CLIPs, and it might be a potential, safe and efficient method for improving the processing properties and broadening the application of insoluble animal-derived proteins.